Reproductive Systems, Transfer and Digestion of Spermatophores in Two Asian Luciolinae Fireflies (Coleoptera: Lampyridae) - Xinhua Fu; Lesley Ballantyne (Insects, 2021)
The internal reproductive anatomy of males and females of two Asian Luciolinae fireflies Emeia pseudosauteri (Geisthardt, 2004) and Abscondita chinensis (L., 1767) is described, and the time course for spermatophore transfer and digestion examined. E. pseudosauteri is sexually dimorphic, with a flightless female, and Abs. chinensis is sexually monomorphic, with the female flighted. Both are monandrous. Possible female accessory glands are described for the first time for both species. An overview of present knowledge of female reproductive anatomy in the Luciolinae reveals males of 18 species in 10 genera may produce spermatophores and permits speculation about spermatophore production in another 16 genera.